2021
DOI: 10.1021/acsestwater.1c00104
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Groundwater Discharge Releases CO2 to a Coral Reef

Abstract: Submarine groundwater discharge (SGD) flows into coral reefs. In volcanically active areas, the incoming groundwater is typically CO2-rich which can alter the carbon balance and views on how coral reefs function at prevailing high CO2. We quantified dynamic hydrothermal SGD and CO2 fluxes to a Philippine coral reef over a spring-neap tidal cycle. SGD rates, with mean of 35 cm d–1 and 5–95% range of 0–147.8 cm d–1. The groundwater-CO2 fluxes (266 mmol m2 d–1; range: 0–1111 mmol m2 d–1) were up to ∼300-fold larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The ratio between SGD fluxes and the volume of their receiving water bodies (SGD/V) has a very good linear relationship ( R 2 = 0.83, p < 0.001) with the average seawater pH decline rates in each receiving water body (Figure 2). The correlation is even better ( R 2 = 0.92, p < 0.05) in the four semi‐closed bays, which partially demonstrate the close relationship between SGD and seawater pH decline (Cardenas et al., 2019; Correa et al., 2021; Wang et al., 2014).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The ratio between SGD fluxes and the volume of their receiving water bodies (SGD/V) has a very good linear relationship ( R 2 = 0.83, p < 0.001) with the average seawater pH decline rates in each receiving water body (Figure 2). The correlation is even better ( R 2 = 0.92, p < 0.05) in the four semi‐closed bays, which partially demonstrate the close relationship between SGD and seawater pH decline (Cardenas et al., 2019; Correa et al., 2021; Wang et al., 2014).…”
Section: Resultsmentioning
confidence: 78%
“…In addition to the implications, some direct observations also confirmed the abovementioned conclusion. For example, through continuous monitoring of seawater carbonate chemistry and SGD geochemical tracers (radium and radon isotopes), some studies have found covariation between SGD and short‐term seawater pH variations (diurnal or spring‐neap tidal cycle) indicating the direct links between SGD and seawater pH (Cardenas et al., 2019; Cardenas et al., 2019; Santos et al., 2011; Wang et al., 2014) In addition, the low‐pH groundwater delivered by SGD influences the coral reef significantly (Correa et al., 2021). Despite its importance, the role of SGD in long‐term coastal acidification is overlooked since most of the relevant studies merely focus on the river discharge, air‐sea CO 2 exchange, and internal biogeochemistry in the water column and neglect the influences of SGD (W.‐J.…”
Section: Introductionmentioning
confidence: 99%
“…FSGD has local ecological impacts on e.g. seagrass (Carruthers et al, 2005), corals (Oehler et al, 2019;Correa et al, 2021;Oberle et al, 2022), phytoplankton (Rodellas et al, 2015;Sugimoto et al, 2017;Waska and Kim, 2010), mollusc (Hwang et al, 2010), meio/macrofauna (Zipperle and Reise, 2005;Kotwicki et al, 2014;Grzelak et al, 2018) and fish populations (Fujita et al, 2019;Pisternick et al, 2020). These influences are often triggered by nutrient and carbon inputs into the submarine environment Böttcher et al, 2022).…”
Section: Environmental Impacts and Resource Prospectsmentioning
confidence: 99%
“…Likewise, F atm was indirectly estimated [42] based on gas transfer velocity (calculated using data on wind speed obtained for Avalon from NOAA's National Centers for Environmental Information website and the temperature-dependent Schmidt number [43]), radon concentrations in water and air, and the Ostwald solubility coefficient [22]. After accounting for F tide , F sed, and F atm , F mix was calculated as the maximum negative radon fluxes over time [44], considering it a radon sink only when the net dI/dt (dI/dt that accounts for F tide , F sed, and F atm ) was negative (Figure 3). Importantly, this approach provides a lower limit of F SGD because mixing could not be reasonably quantified when the net dI/dt was positive.…”
Section: Radon Mass Balance Modelmentioning
confidence: 99%